Part 1: Imaging findings of common immune checkpoint inhibitor‐related adverse effects. Issue 4 (4th March 2022) - Noë, Geertje; Cardin, Anthony; Lasocki, Arian
Abstract: Over the last decade or so, immunotherapy and in particular immune checkpoint inhibitors have become common in the treatment of numerous cancers and have revolutionised oncology. The unique mechanisms of these agents has resulted in novel tumour response patterns and also new drug‐related toxicities, both of which can have specific findings on imaging. The widespread and increasing use of these agents means these findings are now encountered across many radiology practices beyond just specialist oncology units. This pictorial essay aims to describe and illustrate imaging findings associated with common and important immune‐related adverse events as a result of treatment with immune checkpoint inhibitors.